Surface roughness analysis (RA) in the machining of Poly-Ether-Keton (PEEK) for tailored implants - Calvo-Correa, M. P.; Benitez-Forero, J. A.; Cortés-Rodríguez, C. J. (Revista Mexicana de Ingenieria Biomedica, 2017)
The objective of this study is determinate the values of cutting speed, feed along and the machining strategy to get optimal values of roughness Ra for the machining of PEEK, polyetheretherketone, to get to get differentiation, proliferation and adhesion for mesenchymal for the development of individualized tailored prosthesis. According to literature to get those cellular process the superficial roughness must have a value Ra of 1 μm to 3 μm, also, if more anisotropic surface, more adhesion of cells. To determinate the recommended roughness Response Surface Methodology was used, the region of operability was: cutting speed 60 m/min to 90 m/min, feed along 900 mm/min to 1500 mm/min and a cutting strategy of Raster and Spiral. In this investigation the conclusion was that the cutting parameter to get the recommended roughness Ra for the elaboration of tailored prosthesis is feed along of 1500 mm/min and cutting speed of 90 m/min, machining with Raster strategy, for those parameters the roughness was of 2,7 μm.